Human resource management of Kuehne+Nagel Ltd and recommendations on its improvement - Nabil, Ashirul Ikhoan Hasan (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.